Development Of A Technical Instrument For Kicks And Punches For Female Taekwondo Kyorugi Athletes Aged > 17 Years That Suits Competition And Training Needs - Rizki Nur Fadilah (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2025)
The aim of this research is to develop and compile a valid and reliable taekwondo technical skill test instrument for female senior kyorugi athletes > 17 years old that suits the needs in competitions and training, and to compile and develop a test instrument that has norms and standard value conversions. The development method in this research is using Planning, Production, and Evaluation (PPE) development research. The subjects in this research were 20 people who had participated in inter- regional, provincial and even national competitions. The data collection technique in this research uses design (Richey and Klein, 2009). (1) Planning, (2) Production, and (3) Evaluation. This research produces a product, namely in the form of a series of technical manuals on taekwondo technical skills test instruments that are valid and reliable for female senior kyorugi athletes > 17 years old which are in accordance with the needs in competitions and training and norms as well as standard value conversions, which consist of (1 ) SOP instructions for implementing techniques for testing and measuring kicks in Peta Chagi, (2) SOP instructions for implementing techniques for testing and measuring Pyejoek kicks, and (3) instructions for implementing techniques for testing and measuring punches (Jireugi or Jumoek). Keywords: Taekwondo techniques, test instrument development, Kyorugi